A single-center retrospective study with 1-year follow-up after CEA in patients with severe carotid stenosis with contralateral carotid artery occlusion - Yuan, Wanzhong; Huo, Ran; Ma, Kaiming; Han, Yunfeng; Yin, Xiaoliang; Yang, Jun; Zhao, Xihai; Wang, Tao (Frontiers in Neurology, 2022)
Objective: To analyze the risk factors associated with adverse events after carotid endarterectomy (CEA) in patients with unilateral severe carotid stenosis and contralateral occlusion. Methods: Patients were recruited for CEA between August 2014 and February 2020. CEA was performed under general anesthesia. The carotid clamp time (CCT; long CCT: >20 min) is defined as the period between clamp-on and clamp-off for the stenotic carotid artery. The perioperative factors and postoperative adverse events were recorded. All patients were followed up for one year after CEA. Results: Sixty subjects (65.8 ± 7.2 years; 54 males) were included. Patients with adverse events had significantly longer CCT than those without adverse events (60% vs. 40%, P = 0.013). Univariate logistic regression analysis showed that a history of diabetes was significantly associated with adverse events (OR, 0.190; 95% CI, 0.045-0.814; P = 0.025); long CCT was significantly associated with adverse events (OR, 8.500; 95% CI, 1.617-44.682; P = 0.011). After adjusting for confounding factors, including age, sex, BMI, diabetes, PSV, long CCT, nonuse of shunt, and history of stroke or TIA, the associations between diabetes and adverse events (OR, 0.113; 95% CI, 0.013-0.959; P = 0.046) were statistically significant; the associations between long CCT and adverse events (OR, 1.301; 95% CI, 1.049-1.613; P = 0.017) were statistically significant. Conclusions: A longer carotid clamp time (>20 minutes) and a history of diabetes may increase the risk of adverse events in patients with unilateral severe carotid stenosis and contralateral occlusion after CEA. With good preoperative evaluation and intraoperative monitoring, the use of shunts may not be needed intraoperatively in patients with unilateral severe carotid stenosis and contralateral occlusion.